Effect of Salivary Exosomal miR-25-3p on Periodontitis With Insulin Resistance - Byun, Jin-Seok; Lee, Ho Yeop; Tian, Jingwen; Moon, Ji Sun; Choi, Jaejin; Lee, Sang-Hee; Kim, Yong-Gun; Yi, Hyon-Seung (Frontiers in Immunology, 2022)
Periodontitis is caused by an oral microbial dysbiosis-mediated imbalance of the local immune microenvironment, which is promoted by insulin resistance and obesity. The prevalence and severity of periodontitis is higher in patients with type 2 diabetes than in healthy individuals, possibly because of differences in immune response. The level of glycemic control also affects the saliva profile, which may further promote periodontal disease in diabetes patients. Therefore, we compared the salivary exosomal miRNA profiles of patients with type 2 diabetes with those of healthy individuals, and we evaluated the role of exosomal miRNA on the progression of periodontitis by analyzing immune cells in both periodontal tissues and regional lymph nodes from mice with periodontitis. We found that diet-induced obesity and insulin resistance increased the population of infiltrating pro-inflammatory immune cells in the gingiva and regional lymph nodes of these mice. We also found that exosomal miR-25-3p in saliva is highly enriched in obese patients with type 2 diabetes. We identified CD69 mRNA as a miR-25-3p target that regulates both the activation of γδ T cells and the inflammatory response. Inhibition of miR-25-3p attenuated activation of γδ T cells in vitro and prevented the local in vivo inflammatory response in mice with periodontitis, diet-induced obesity, and insulin resistance. Finally, we showed that suppression of interleukin 17-mediated local inflammation by miR-25-3p inhibitor alleviated ligature-induced periodontal alveolar bone loss in mice. Taken together, these data suggest that exosomal miR-25-3p in saliva contributes to the development and progression of diabetes-associated periodontitis. Discovery of additional miR-25-3p targets may provide critical insights into developing drugs to treat periodontitis by regulating γδ T cell-mediated local inflammation.